2012
DOI: 10.1007/s12254-012-0330-7
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of anemia correction during radiotherapy and chemoradiation

Abstract: Th e eff ect of radiotherapy depends on optimal tumour oxygenation, as tumour hypoxia impairs the production of radiation-induced cytotoxic free radicals resulting in less tumour cell kill. Th e range of haemoglobin levels optimal for tumour oxygenation is 12-14 g/dl in women and 13-15 g/dl in men. It appears reasonable to elevate the haemoglobin level in anaemic cancer patients into this optimal range. Th is may be achieved with red blood cell transfusions (RBCT) or erythropoiesis stimulating agents (ESAs). H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In cervical cancer, several studies have found low hemoglobin (Hg) levels before and during radiation therapy to be strongly prognostic for local control and survival [20,21]. Although the relationship between anemia and poor prognosis is still unclear, one explanation may be that anemic hypoxia impairs the production of cytotoxic free radicals, limiting the extent to which radiation therapy can reduce tumor size [22]. More recently, however, a number of reports have questioned the potential causality of this relationship [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In cervical cancer, several studies have found low hemoglobin (Hg) levels before and during radiation therapy to be strongly prognostic for local control and survival [20,21]. Although the relationship between anemia and poor prognosis is still unclear, one explanation may be that anemic hypoxia impairs the production of cytotoxic free radicals, limiting the extent to which radiation therapy can reduce tumor size [22]. More recently, however, a number of reports have questioned the potential causality of this relationship [23,24].…”
Section: Introductionmentioning
confidence: 99%